Linking tumor hypoxia with VEGFR2 signaling and compensatory angiogenesis: Glycans make the difference - Croci, Diego O (Landes Bioscience, 2014)
Although blocking vascular endothelial growth factor (VEGF) signaling is clinically beneficial in certain cancers, tumor regrowth in treated patients suggests that compensatory angiogenic programs may limit the efficacy of anti-VEGF treatment. We found that association of galectin-1 with complex N-glycans on VEGFR2 links tumor hypoxia to VEGFR2 signaling and preserves angiogenesis in response to VEGF blockade.